2020
DOI: 10.1182/bloodadvances.2020001756
|View full text |Cite
|
Sign up to set email alerts
|

JAK inhibition synergistically potentiates BCL2, BET, HDAC, and proteasome inhibition in advanced CTCL

Abstract: Cutaneous T-cell lymphoma (CTCL) is a malignancy of skin-homing T lymphocytes that is more likely to involve the peripheral blood in advanced stages. For such patients with advanced disease, there are few available systemic treatment options, and prognosis remains poor. Exome sequencing studies of CTCL have suggested therapeutic targets, including within the JAK/STAT pathway, but JAK inhibition strategies may be limited by patient-specific mutational status. Because our recent research has highlighted the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Responders to venetoclax monotherapy for chronic lymphocytic leukemia had progression-free survival of approximately 70% at 12 to 15 months. 7 , 9 , 10 Evidence of clinical efficacy in our patient, supported by our previously reported in vitro viability assays and CTCL patient malignant cell BCL-2 expression profiles, 4 , 5 suggests venetoclax as a potential oral therapy for CTCL that warrants further investigation of clinical safety, dosing, and efficacy.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Responders to venetoclax monotherapy for chronic lymphocytic leukemia had progression-free survival of approximately 70% at 12 to 15 months. 7 , 9 , 10 Evidence of clinical efficacy in our patient, supported by our previously reported in vitro viability assays and CTCL patient malignant cell BCL-2 expression profiles, 4 , 5 suggests venetoclax as a potential oral therapy for CTCL that warrants further investigation of clinical safety, dosing, and efficacy.…”
Section: Discussionsupporting
confidence: 76%
“… 3 We also recently reported that patient-derived CTCL cells exhibited variable sensitivity to venetoclax, with a portion showing picomolar-range 50% inhibitory concentrations, and that venetoclax sensitivity was correlated with baseline BCL-2 expression. 4 , 5 Herein, we present a CTCL patient with skin and blood involvement treated with daily venetoclax.…”
Section: Introductionmentioning
confidence: 99%
“…Established tumor cell lines may be passaged in vitro, frozen and stored for later use, and transplanted into syngeneic and/or immunecompromised laboratory animals to grow as tumors. Limitations to the use of passaged tumor cell lines include the potential for further development and selection of mutations in vitro, and that limited lines may not reflect the heterogeneity of disease in patients (Gillet et al, 2013;Yumeen et al, 2020). Alternatively, primary tumor cell isolates from patients may be short-term cultured, and their genomic and transcriptional profiles are likely a more accurate representation of the spectrum of disease.…”
Section: Materials and Equipment For High-throughput Drug Screeningmentioning
confidence: 99%
“…Chromatin organization can be altered in malignant cells to result in an aberrant transcriptional profile, and thus DNA methylation or histone deacetylation can also be targeted. (Created with biorender.com and adapted with permission from Yumeen et al, 2020). GPCR, G-protein coupled receptor; HDAC, histone deacetylase; SMI, small molecule inhibitor; STAT, signal transducer and activator of transcription; TRAIL, TNF-related apoptosis-inducing ligand.…”
Section: Evaluating Synergy In Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation